2003
DOI: 10.1590/s1519-566x2003000400009
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização molecular de populações de Euseius citrifolius Denmark & Muma e Euseius concordis (Chant) (Acari: Phytoseiidae) utilizando o seqüenciamento das regiões ITS1 e ITS2

Abstract: Mites have usually been identified by their morphological characteristics. However, morphological evidences are not always sufficient to distinguish between closely related species, leading taxonomists to consider additional ecological, biological and, more recently, molecular characteristics in this process. The molecular characterization of populations of Euseius citrifolius Denmark & Muma and Euseius concordis (Chant) was done by sequencing the internal transcribed spacers ITS1 and ITS2 using the P1 (5'-AGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The lack of oviposition by unmated females has been observed for the phytoseiid mites studied to date (e.g., see Croft, 1970;Moraes and McMurtry, 1981;Noronha et al, 2003). In this study, unmated females from both La Réunion and Roraima, Brazil populations did not oviposit during their entire life cycle, which demonstrated that crossing is a prerequisite for oviposition.…”
Section: Discussionsupporting
confidence: 68%
“…The lack of oviposition by unmated females has been observed for the phytoseiid mites studied to date (e.g., see Croft, 1970;Moraes and McMurtry, 1981;Noronha et al, 2003). In this study, unmated females from both La Réunion and Roraima, Brazil populations did not oviposit during their entire life cycle, which demonstrated that crossing is a prerequisite for oviposition.…”
Section: Discussionsupporting
confidence: 68%
“…Hence, molecular and other tools may be helpful for taxonomic identification ). These techniques have allowed researchers to look beyond morphological similarities by searching for genetic and other differences to answer taxonomic questions (Navajas et al 1996(Navajas et al , 1998Hinomoto et al 2001Hinomoto et al , 2007Jeyaprakash and Hoy 2002;Noronha et al 2003;Ramadan et al 2004;Klimov et al 2004;Tixier et al 2006aTixier et al , 2010Ros and Breeuwer 2010;Okassa et al 2009Okassa et al , 2010Okassa et al , 2011Kanouh et al 2010). Here, we address the question whether predatory mites collected from different geographic localities and previously identified as Neoseiulus baraki Athias-Henriot represent more than one closely related species.…”
Section: Introductionmentioning
confidence: 94%
“…Little is known on the reliability of characters used for Phytoseiidae species discrimination because intraspecific variations are not well defined. To assist diagnostics, molecular markers have been recently applied within Phytoseiidae (Jeyaprakash & Hoy, 2002;Noronha et al, 2003;Tixier et al, 2006aTixier et al, , b, 2008aTixier et al, , 2010Okassa et al, 2009Okassa et al, , 2010Kanouh et al, 2010). However, because morphological analyses require distinct characters, molecular analyses require the accurate characterization of intraspecific variations to discriminate species from populations of the same species (Wiens & Servedio, 2000;Dayrat, 2005;Meier, 2008;Cardoso, Serrano & Vogler, 2009).…”
Section: Introductionmentioning
confidence: 99%